Determinan Investasi Portofolio Asing di Indonesia - Zulfa Mutiarani; Doni Satria (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the influence of external and internal factors on foreign portfolio investment in Indonesia. Variables used are the Fed Rate, global risk, exchange rate volatility, and interest rates. The data used is a sequence of data for the period 1993Q1-2024q4. The analysis method used is Error Correction Model (ECM) to identify short-term and long-term relationships between variables. The results showed that in the short term the variable Fed Rate and global risks have a significant negative effect, while the volatility of exchange rates and interest rates did not show a significant effect on foreign portfolio investment in Indonesia. In the long run, all variables have a significant effect on foreign portfolio investment in Indonesia. The Fed Rate, global risks, and interest rates have a negative influence, while exchange rate volatility has a positive effect. These results indicate that external factors predominantly influence the flow of foreign portfolio investment in Indonesia.